PELECEHAN SEKSUAL DALAM HUKUM INTERNASIONAL - Diah Mutiara Dewi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Sexual harassment in international law is a deep and complex issue, affecting thousands of people worldwide every year. This article aims to cover and analyze the challenges and prospects for global protection of victims of sexual violence. Through a comprehensive study of various international legal instruments, including the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), the Convention on Human Rights, and various regional agreements and UN resolutions, the authors identify the important role played by international organizations in efforts to combat sexual harassment. This article also challenges the challenges faced in law enforcement and accountability of perpetrators of sexual harassment at the international level. Lack of consistency in the definition and punishment of sexual insults across countries, as well as limiting victims' access to the legal system, are obstacles in dealing with this problem effectively. However, despite these challenges, this article offers positive prospects regarding the advocacy role of civil society and the increasing international awareness of the issue of sexual disappearance. Beyond national boundaries, international factories in addressing sexual harassment are becoming increasingly important, with the ultimate goal of creating a global environment that is safe and free from sexual violence.